Point‐of‐Care Ultrasound in Undergraduate Urology Education: A Prospective Control‐Intervention Study. (24th February 2018) - Olszynski, Paul; Anderson, Jordan; Trinder, Krista; Domes, Trustin
Abstract : Objectives: The effect of point‐of‐care ultrasound (US) training on clinical reasoning in undergraduate medical education remains largely unknown, with concerns arising about possible confusion among learners when such clinical tools are introduced too early. We studied the effect of a urology point‐of‐care US module on the performance of questions designed to assess clinical reasoning in urinary tract obstruction and voiding dysfunction. Methods: All second‐year medical students at the University of Saskatchewan (Regina [n = 36] and Saskatoon [n = 61]) were enrolled in the study. Each cohort participated in the urology point‐of‐care US module concurrently with its Foundations in the Kidney and Urinary Tract course. The Regina cohort completed the point‐of‐care US module 1 week before the Saskatoon cohort, thus allowing for a control‐intervention comparison of script concordance question scores to evaluate the effect that the urology point‐of‐care US module had on clinical reasoning skills. Secondary outcomes included program evaluation metrics, such as overall course performance, urology point‐of‐care US objective structured clinical examination performance, and student course evaluation data. Results: The introduction of the urology point‐of‐care US module was not associated with a deterioration in scores on script concordance questions. There were no statistically significant differences between the Regina and Saskatoon students in their responses to the script concordance questions. There were statistically significant increases in student self‐reported achievement of learning objectives, with the effect size being medium to large (Cohen d, 0.5–0.8). Conclusions: Point‐of‐care US training complements standard undergraduate classroom teaching of urology. Students effectively learned the skills to apply point‐of‐care US in their assessment of patients, and this process did not interfere with achieving the course objectives.